Analysis of Labor Absorption in the Dodol Industry in Suranadi Village, Narmada District, West Lombok Regency - Ningsih, Saptia; Fuadi, Helmy; Yuniarti, Titi (The Eastasouth Management and Business, 2024)
This research aims to analyze the application of labor in the dodol industry in Suranadi Village, Narmada District, West Lombok Regency. Data comes from 13 respondents who are owners of the dodol industry with the data collection method used is the census method and questionnaire distribution techniques as data collection tools. The analytical instrument employed is multiple linear regression, accompanied by the classical assumption tests, which encompass three evaluations: the normality test, multicollinearity test, and heteroscedasticity test, as well as the statistical assessment known as the simultaneous test (F test). partial test (t-test) and coefficient of determination. The research results show that the production value and capital wage variables have a significant value of 0.000 <0 05, which means they are simultaneous. has a significant influence on labor absorption. Individually, the wage variable has a significant value of 0.043 < 0.05. the production value variable is 0.040 < .05, and the capital variable is 0.043 < 0.05, which means that partially the wages, production value and capital variables have a significant influence on the application of labor force.